2014
DOI: 10.5468/ogs.2014.57.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated pulmonary embolism during the peripartum period: An 8-year experience at a single center

Abstract: ObjectiveThe purpose of this study was to estimate the incidence, timing of onset, risk factors, and mortality rate of pregnancy-associated pulmonary embolism (PAPE).MethodsWe analyzed PAPE cases that occurred between January 2005 and December 2012 at Cheil General Hospital & Women's Healthcare Center. Those cases that were not confirmed by computed tomography scan or were confirmed as amniotic fuid embolisms were excluded. We analyzed various risk factors such as previous surgery, mode of delivery, maternal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
1
14
1
1
Order By: Relevance
“…The low cumulative incidence may be truly low, consistent with a report from South Korea which described a much lower VTE rates of 0.82 per 10 000 deliveries as compared to the West 6 . However, subsequent paper shows that the incidence rate increased to 2.3 (per 10 000 deliveries), 14 underscoring the possibility of underdiagnosis from low awareness towards thrombotic diseases or low clinical suspicion due to perceived low incidence 15,16 …”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The low cumulative incidence may be truly low, consistent with a report from South Korea which described a much lower VTE rates of 0.82 per 10 000 deliveries as compared to the West 6 . However, subsequent paper shows that the incidence rate increased to 2.3 (per 10 000 deliveries), 14 underscoring the possibility of underdiagnosis from low awareness towards thrombotic diseases or low clinical suspicion due to perceived low incidence 15,16 …”
Section: Discussionsupporting
confidence: 78%
“…with a perinatal mortality rate of 44 per 1000 12 . Our neonatal outcomes are not adverse even though we had higher preterm births (37.5%) compared to another Korean study (23.1%) 14 . However, our sample size is too small to generalize and future larger scale studies are needed to determine the perinatal mortality rate of pregnancy‐associated PE.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…8,9 It has been found that the incidence of VTE increases about 4-5 times in pregnant women and 20 times in the postpartum period. [5][6][7][9][10][11][12][13][14][15] This risk may be even higher: 1 study demonstrated a 60-fold increase in the risk of VTE in the first 3 months after delivery compared with non-pregnant women. 16 In developing countries, the incidence of VTE has increased, with a ratio of 1 case per every 16 pregnancies per year.…”
Section: Incidence Of Venous Thromboembolismmentioning
confidence: 99%
“…4,6,10,13,17 Given the high maternal mortality due to PTE, early diagnosis and treatment should be prioritized. 7…”
Section: Incidence Of Venous Thromboembolismmentioning
confidence: 99%